Studi Deskriptif Pengaruh Metode Bercerita Bilingual Terhadap Minat Belajar Anak Usia Dini - Wirsa, Khairani; Saridewi, Saridewi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
Children learning process in kindergarten is very influential in early childhood development. Therefore, a teacher expected to be able to make variation of learning media and interesting learning method, so the objective of the learning is achieved well. The background of this study is lack of interesting methods used by teacher to improve children's focus in learning and children's interest in foreign languages. So, the researcher is interested to do a research about bilingual storytelling methods. According to experts the storytelling method is one of the most interesting method in learning. The type of research is the literature study with data collection techniques by reviewing books, journals, magazines and articles related to research topics. The result of the research, the bilingual storytelling method is an interesting method for children so it could increase children's learning interest. Therefore the aim of the learning could be achieved as expected.